2015
DOI: 10.1179/2054892315y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anthraquinone dye colourants in red fibres from an Ohio Hopewell mound site by direct analysis in real time mass spectrometry

Abstract: Among prehistoric native groups of North America, the Ohio Hopewell was a particularly notable cultural manifestation that prevailed during the Middle Woodland Period (ca. 2100 -1500 BP). The group is defined by the construction of elaborate burial mounds, evidence of ritual burning and cremation ceremonies, The presence of anthraquinones in these Ohio Hopewell textiles, and the absence of the bloodroot alkaloids, supports previous studies suggesting the prehistoric use of Galium species as dye plants in Easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…A form of electrospray ionization, paper spray makes molecules that are not readily ionized with DART accessible in a low-volume format. The Armitage group has pioneered the use of DART-MS for analysis of natural dyes for applications to ancient textiles [9,[19][20][21][22] and other cultural heritage materials [23][24][25]. While paper spray has been used by others for characterizing both natural and artificial colorants in food and beverage [26,27], this is the first instance of which we are aware for its use in heritage science applications.…”
Section: Introductionmentioning
confidence: 99%
“…A form of electrospray ionization, paper spray makes molecules that are not readily ionized with DART accessible in a low-volume format. The Armitage group has pioneered the use of DART-MS for analysis of natural dyes for applications to ancient textiles [9,[19][20][21][22] and other cultural heritage materials [23][24][25]. While paper spray has been used by others for characterizing both natural and artificial colorants in food and beverage [26,27], this is the first instance of which we are aware for its use in heritage science applications.…”
Section: Introductionmentioning
confidence: 99%
“…Direct analysis in real time (DART) ionisation coupled to time-of-flight mass spectrometry has been demonstrated as a rapid, simple method for the identification of dye colourants on cotton (Selvius DeRoo and Armitage 2011; Geiger, Armitage and Selvius DeRoo 2012) as well as on wool and silk fibres (Day, Selvius DeRoo and Armitage 2013). Most recently, DART-MS has shown that textile fibres from the Seip Mound group in Ohio were consistent with the use of anthraquinone dyes obtained from Galium species but did not show any evidence of benzoisoquinoline alkaloids from bloodroot (Sanguinaria canadensis) (Armitage, Day and Jakes 2015).…”
Section: Dart-ms For the Identification Of Dyes In Historic Textile Fmentioning
confidence: 99%
“…2013; DeRoo and Armitage 2014; Armitage et al . 2015a, 2015b, 2019; Armitage and Jakes 2015), residues (Hopkins and Armitage 2012; Fraser et al . 2013; Kaktins et al .…”
Section: Methodsmentioning
confidence: 99%